2019
DOI: 10.3390/pr7060327
|View full text |Cite
|
Sign up to set email alerts
|

The Influence and Optimization of Geometrical Parameters on Coast-Down Characteristics of Nuclear Reactor Coolant Pumps

Abstract: Coast-down characteristics are the crucial safety evaluation factors of nuclear reactor coolant pumps. The energy stored at the highest moment of inertia of the reactor coolant pump unit is utilized to maintain a normal coolant supply to the core of the cooling loop system for a short period of time during the coast-down transition. As a result of the high inertia moment of the rotor system, the unit requires a high reliability of the nuclear reactor coolant pump and consumes considerable energy in the start-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was found that the ow state of the uid medium can be signi cantly improved, the ow loss can be reduced, the idling time can be increased, and the pressure pulsation amplitude within each sub frequency range can be reduced. In order to prolong the idling time of the RCP, Zhao [11] optimized the hydraulic performance of the RCP through orthogonal test, and obtained the optimal geometric parameter combination of the impeller by multiple linear regression. Xie [12] put forward a mathematical model of speed and ow during idling of RCP, predicted the mathematical relationship of hydraulic performance of guide vanes under different parameters, and veri ed it with idling test data.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the ow state of the uid medium can be signi cantly improved, the ow loss can be reduced, the idling time can be increased, and the pressure pulsation amplitude within each sub frequency range can be reduced. In order to prolong the idling time of the RCP, Zhao [11] optimized the hydraulic performance of the RCP through orthogonal test, and obtained the optimal geometric parameter combination of the impeller by multiple linear regression. Xie [12] put forward a mathematical model of speed and ow during idling of RCP, predicted the mathematical relationship of hydraulic performance of guide vanes under different parameters, and veri ed it with idling test data.…”
Section: Introductionmentioning
confidence: 99%